Land Use Analysis with Odonata Diversity and Composition using the ArcGIS in Malang and Batu, East Java - Albert Ulul Albab; Amin Setyo Leksono; Bagyo Yanuwiadi (Jurnal Pembangunan dan Alam Lestari)
This study aims to analyze the diversity, composition, and community structure of odonata in the highland and lowland ecosystems and the type of lotic and lentic waters and analyze the description of land use and its relationship with diversity odonata. There are 8 research locations namely Sumber Maron, Sumber Sirah, Sumber Taman, Bureng River, Umbul Gemulo, Arboretum, Coban Rais River, Coban Talun River. Measurement of biotic and abiotic factors in odonata habitat and land use analysis using GPS and ArcGIS program ver 10.5, data analysis using the Shannon Wiener diversity index (H'), evenness index (E), Important Value Index (IVI), and similarity index Bray-curtis. The results showed that the total number of Anisoptera in lotic aquatic ecosystems was 619 individuals divided into 13 species from 3 families, in the lenticular aquatic ecosystem was 533 individuals divided into 15 species from 3 families. This study concludes that the diversity of species in the highlands is higher than in the lowlands, and the diversity in the lentic ecosystem is higher than that of the lotik ecosystem and odonata has its own tolerance to land use as their habitat especially with minimal human disturbances.